(untitled) (Research, Society and Development, 2022)
Introduction: The prevalence of Alzheimer’s disease (AD) and Parkinson’s disease (PD) tends to increase with the aging population. Currently, the therapeutic schemes for these diseases cannot achieve a cure and are also not frequently updated, which highlights the need for other options to improve the quality of life of these patients. Given that these dementia syndromes have a multifactorial etiology, diet, through coffee, has shown significant evidence in neuronal degeneration, which is one of the main aspects altered in the development of these pathologies. Methodology: This is an integrative review, which sought to answer what the possible effects of caffeine as a protective factor in the development and progression of AD and PD, in the databases: Virtual Health Library (VHL) National Library of Medicine (PubMed MEDLINE) and Scientific Electronic Library Online (Scielo). Results and Discussion: Caffeine acts in the central nervous system (CNS) by mimicking the adenosine receptors, more concentrated in the A1R and A2aR receptors. As a competitive antagonist, caffeine could possibly reduce the processes of b-amyloid plaque formation in AD and reduce neuroinflammation and neurodegeneration in PD, besides other possible mechanisms. Conclusion: The delimitation of a consensus on the dose/effect relation resulting from the use of caffeine is difficult to establish and a consensus is not yet observed; however, it is possible to observe that an intake between 200mg to 511mg per day could bring beneficial effects both in PD and in AD, overcoming the possible side effects.